Healthcare practitioners’ views of postnatal depression: a qualitative synthesis - Siti Roshaidai Mohd Arifin,; Cheyne, Helen; Maxwell, Margaret (Penerbit Universiti Kebangsaan Malaysia, 2019)
The World Health Organisation recommends healthcare practitioners to equip themselves with appropriate skills to assess the psychological distress in women attending the antenatal and postnatal healthcare. Nevertheless, little is known about the healthcare practitioners’ perceptions of postnatal depression and its management. The aims of this review were: (1) to explore the experiences of healthcare practitioners in caring for women with postnatal depression in different countries and (2) to identify any qualitative study conducted in Malaysia regarding the healthcare practitioners’ perceptions of postnatal depression. To achieve these objectives, a qualitative synthesis of studies reporting the healthcare practitioners’ experience of managing women with postnatal depression was conducted. A search in CINAHL, PubMed, MEDLINE, PsycINFO and ASSIA databases was performed using specific keywords and published peer-reviewed articles from 2006 to 2016 were screened for inclusion criteria. A total of 15 relevant studies were identified and reviewed. The studies included were conducted in eight different countries: America, Australia, United Kingdom, Brazil, Canada, Greek, Mexico and Slovenia. No study conducted in Malaysia was found. This review suggestedthat the experiences of managing women with postnatal depression were relatively similar among the healthcare professionals in different countries. The main limitations reported by the healthcare practitioners were the lack of resources on maternal mental health and the absence of policy regarding the management of postnatal depression. Further research should investigate how Malaysian healthcare practitioners perceive postnatal depression and their roles in its management to provide more insights into the current clinical practice in Malaysia for postnatal depression.